The main features of epidemiology and clinical-immunological interactions of infections caused by herpes viruses and opisthorchiasis at residents of Tomsk - N. A. Cherevko; L. M. Ogorodova; M. V. Vasiliyeva (Бюллетень сибирской медицины)
To elucidate the epidemiological, clinical and immunological characteristics of infections caused by herpes viruses and opistorhisami in the etiology and pathogenesis of allergic diseases, we examined 350 residents of Tomsk. The high frequency of infection among residents of Tomsk with herpes simplex virus types 1 and 2, in comparison with the average for Russia in all the groups studied. The level of sensitization and the different severity of allergic reactions in the studied sample was 74%. In groups of volunteers infected with opisthorchiasis, the prevalence of allergic sensitization is higher than the group infected with herpes. The combination of allergic sensitization in herpes-infected patients is associated with the risk of recurrent course of infection, ie with the frequency and severity of clinical manifestations of the latter.